2023
DOI: 10.26509/frbc-wp-202304
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate implications of heterogeneous inflation expectations: the role of individual experience

Abstract: We show that inflation expectations are heterogeneous and depend on past individual experiences. We propose a diagnostic expectations-augmented Kalman filter to represent consumers’ heterogeneous inflation expectations-formation process, where heterogeneity comes from an anchoring-to-the-past mechanism. We estimate the diagnosticity parameter that governs the inflation expectations-formation process and show that the model can replicate systematic differences in inflation expectations across cohorts in the US.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…The higher volatility in inflation expectations of the younger households is consistent with the findings in Malmendier and Nagel (2016), who document that younger people revise their expectations "more strongly" than older people in response to inflation surprises. In a similar vein, Pedemonte et al (2023) find that since the inflation surge of 2021, older individuals have higher inflation expectations, consistent with their forming their expectations by drawing on their memory of the higher inflation they experienced in the 1970s.…”
Section: Introductionsupporting
confidence: 52%
“…The higher volatility in inflation expectations of the younger households is consistent with the findings in Malmendier and Nagel (2016), who document that younger people revise their expectations "more strongly" than older people in response to inflation surprises. In a similar vein, Pedemonte et al (2023) find that since the inflation surge of 2021, older individuals have higher inflation expectations, consistent with their forming their expectations by drawing on their memory of the higher inflation they experienced in the 1970s.…”
Section: Introductionsupporting
confidence: 52%
“…This underscores the importance of effective central bank communication, especially in the context of recent high inflation. Pedemonte et al (2023) find that high disagreement in expectations can make shocks more persistent and more memorable, thus increasing their effect on future expectations. As a result, persistent partisan bias could exacerbate the effects of a negative shock like a high-inflationary episode.…”
Section: Discussion Limitations and Future Researchmentioning
confidence: 80%
“…A recently growing body of literature suggests that individual experiences influence inflation expectation formation-a significant departure from the theoretical assumption that expectations draw from objective evaluations of the economy ("full information rational expectations"). Macroeconomic modeling literature has demonstrated that heterogeneity in consumer expectations can generate over-investment in real assets (Sims, 2009) impact the economy's vulnerability to exogenous shocks (Badarinza & Buchmann, 2011), and make shocks more persistent (Pedemonte et al, 2023).…”
Section: Partisan Perspectives On Inflation: Exploring Bias In Econom...mentioning
confidence: 99%